Stalk-derived carbon dots as nanosensors for Fe3+ ions detection and biological cell imaging - Du, Yongchao; Li, Yaxi; Liu, Yunliang; Liu, Naiyun; Cheng, Yuanyuan; Shi, Qiuzhong; Liu, Xiang; Tao, Zhimin; Guo, Yumeng; Zhang, Jianguo; Askaria, Najmeh; Li, Haitao (Frontiers in Bioengineering and Biotechnology, 2023)
In this study, carbon dots (CDs) were obtained from corn stalk powder by pyrolysis and microwave process. The CDs demonstrate good stability, strong visible fluorescence properties, and biocompatibility. In addition, due to the effective quenching effect of Fe3+ ions, the prepared CDs can be used as fluorescent sensors for the selective detection of Fe3+ ions. The fluorescence quenching showed a good linear relationship with the Fe3+ concentration in the range from 0 to 128 μM, and a low detection limit of 63 nM. More importantly, the CDs have a low cytotoxicity and desirable biocompatibility, allowing the multicolor living cell imaging. Therefore, the conversion of agricultural waste into carbon nanomaterials has great potential to be developed.